Effective Treatment of Industrial Wastewater Contaminated with Mn and Pb using Mesoporous Silica from Yogyakarta Beach - Siti Salamah; Suhendra Suhendra (Universitas Ahmad Dahlan, 2021)
The research was investigated using Yogyakarta beach sand as the main material to synthesize mesoporous silica (MS). The MS usage in the environmental field is mainly to overcome water pollution, contaminated from chemical waste used in industrial productions. In the sol-gel method, the silica from beach sand was extracted and synthesized into MS using a dodecyl amine (DDA) template. MS is used as an adsorbent for manganese (Mn) and lead (Pb) printing liquid waste. MS produced was analyzed with FTIR and surface area analyzer (SAA). The process of waste adsorption used MS weight variables of 1 gr, 2 gr, and 3 gr. The MS was mixed in the waste and stirred with a rotation speed of 120 rpm for 2 hours. The solution was left for 24 hours until separated from the adsorbent. AAS analyzed the resulting liquid, and the adsorbent was dried at 100 Â°C for 24 hours and analyzed by SEM-EDX. The synthesized MS was characterized. It has a surface area of 122.78 m2/gr and a pore diameter of 4.65 nm. The AAS analysis results showed that the wastewater contains Ni <0.076 mg/L and Pb <0.415 mg/L. The SEM-EDX analysis showed that the adsorbent used contains 0.01% Mn, 0.01% Pb, and 0.39% Cu. The research showed that the liquid printing waste analyzed contains nickel, lead, and copper.